Causes of Grade 10 learners' grammatical errors when writing English essays in a school, Moboke Circuit, Mpumalanga Province, South Africa - Komane, Rethabile Mphahlele (My University, 2025)
The purpose of the study was to investigate causes of Grade 10 learners’ grammatical errors when writing English essays at a rural South African high school. The population for the study consisted of 9 secondary schools in the Maboke Circuit, in the Bohlabela District, Mpumalanga Province, South Africa. 20 Grade 10 English First Additional Language learners and three English educators were purposefully sampled to participate in the study. A qualitative research approach was adopted to carry out the study from an interpretivist point of view. Semi-structured interviews and documents were used to collect qualitative data from the sampled teachers and learners respectively. The results of the study revealed evidence of grammatical errors in the learners' essays identifiable as errors in punctuation, word order, tenses, spelling and pronoun use. These errors were found to be caused by lack of resources, learners’ lack of interest in the English language, insufficient English instructional time, home language interference, and limited English vocabulary range. The study recommends increased time allocation for grammar teaching, frequent writing practice, the use of more effective teaching methods, and the use of stimulating teaching and learning materials as possible strategies to ameliorate the learners’ writing challenges.
Thesis (M. (Language Education)) -- University of Limpopo, 2025
Keywords: English first additional language; Language influence; Grammatical errors; Sepedi home language; Teaching strategies; Writing skills; Essay; English language -- Grammar; English essays; English language -- Study and teaching -- South Africa -- Mpumalanga